1997
DOI: 10.1073/pnas.94.3.928
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutations reveal long-range compensatory interactions in the Adh gene of Drosophila melanogaster

Abstract: Long-range interactions between the 5 and 3 ends of mRNA molecules have been suggested to play a role in the initiation of translation and the regulation of gene expression. To identify such interactions and to study their molecular evolution, we used phylogenetic analysis to generate a model of mRNA higher-order structure in the Adh transcript of Drosophila melanogaster. This model predicts long-range, tertiary contacts between a region of the protein-encoding sequence just downstream of the start codon and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Indeed, we find that the mini-white gene, which is present in all of our transformation vectors, shows expression patterns consistent with dosage compensation in the somatic (eye) tissue (Table 3). This is in agreement with previous studies reporting that, in males, X-linked alcohol dehydrogenase (Adh) transgenes show higher expression than those inserted on autosomes (Laurie-Ahlberg and Stam, 1987;Parsch et al, 1997). These findings indicate that the reduced X-linked expression seen for our testis-expressed transgenes is not an artifact of the P-element vector used for transformation, as this pattern is not observed for somatically expressed transgenes.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, we find that the mini-white gene, which is present in all of our transformation vectors, shows expression patterns consistent with dosage compensation in the somatic (eye) tissue (Table 3). This is in agreement with previous studies reporting that, in males, X-linked alcohol dehydrogenase (Adh) transgenes show higher expression than those inserted on autosomes (Laurie-Ahlberg and Stam, 1987;Parsch et al, 1997). These findings indicate that the reduced X-linked expression seen for our testis-expressed transgenes is not an artifact of the P-element vector used for transformation, as this pattern is not observed for somatically expressed transgenes.…”
Section: Discussionsupporting
confidence: 81%
“…None of these minor differences in local structures appear to be sufficient to differentially inhibit the helicase activity of the ribosome, which has been experimentally demonstrated to be capable of melting a highly stable 27-bp helix (À52.1 kcal/mol) without dissociation from the mRNA (Takyar et al 2005). Furthermore, the 7up mutations did not alter any of the putative secondary structural elements identified by previous covariation analysis of multiple Drosophila species or by previous experimental manipulation (Kirby et al 1995;Parsch et al 1997;Carlini et al 2001;Chen and Stephan 2003;Baines et al 2004). We also determined a consensus mRNA secondary structure for Adh coding sequences of 12 Drosophila species from the recent 12 genomes project, using RNAalifold (Gruber et al 2008).…”
Section: Discussionmentioning
confidence: 79%
“…Known cases of epistatic selection in rRNAs and mRNAs are due to one obvious mechanism, Watson-Crick pairing of nucleotides that maintains secondary structure (28)(29)(30). In contrast, studies of second-site intragenic suppression of missense mutations revealed a variety of mechanisms of molecular compensation in proteins (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences may involve mild DM incompatibilities, with some combinations of states having reduced but nonzero fitness. For selection acting on RNAs, such DM incompatibilities can occur even between polymorphic sites within a population (30). However, here we considered mostly lethal DM incompatibilities, because almost all pathogenic mutations causing Mendelian diseases would be lethal to a human under natural conditions, at least when homozygous.…”
Section: Discussionmentioning
confidence: 99%